Boosting English Students’ Writing Skill via Roundtable Strategy - Kasmaini, Kasmaini (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
The purpose of this study is to use a roundtable technique to improve the writing capacity of S1 English education studies students at FKIP UNIB. This study's architecture is based on classroom action studies. It was completed in three cycles. The instruments are a checklist, an observation, and a measure. The results of the checklist revealed that there was an improvement in student activity from cycles 1, 2, and 3. Meanwhile, the observation outcome represented an increase in students' awareness of the roundtable strategy's application from the first to third period. Finally, the test result indicated an improvement in score from cycle 1 to cycle 3 name from 75, 79, and 83.5. The results of the three instruments indicate that the roundtable approach will increase the writing capacity of English education research programme students. This strategy can be used in teaching writing for students.Keywords : boosting English, writing ability, roundtable strategy